Автоматизация районных тепловых станций - Емельянов М. А. Михаил Александрович; Трембицкий В. Я. Виктор Яковлевич; Харин А. В. Александр Викторович; Цысин М. И. Марк Исаакович (Москва, Стройиздат, 1970)
Исключено из фонда НТБ ТПУ